Assessing the Merger of Online Platform Companies: Does it Lead to Monopoly or just Business Expansion? (Analysis of The Merged Company of GoTo) - Sukarmi, Sukarmi; Al-Fatih, Sholahuddin; Tejomurti, Kukuh; Alam, Moch. Zairul (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
Two large digital platform companies, Gojek and Tokopedia, officially merged to form a holding company called the GoTo Group that is considered to have anti-competitive behavior and potentially data monopoly. This article aimed to analyze the adequate response to potential violations of the Prohibition of Monopolistic Practices and Unfair Business Competition Regulation and legal issues related to consumer data monopoly issues. This article uses normative legal research with the conceptual research and statute approach. The result shows that it is necessary to define “relevant markets” and the “substituted products” to determine the existence of unfair business competition in the Gojek-Tokopedia merger. It requires analyzing the consumer behavior in other marketplaces other than Tokopedia; when consumers do not